Artificial intelligence: Moving forward to a new era of education / Dr Salfarina Ramli and Prof. Vyacheslav Dushenkov - Ramli, Salfarina; Dushenkov, Vyacheslav (Faculty of Pharmacy, 2023)
Over the past two decades, the landscape of higher education has undergone a profound transformation, primarily driven by technological advancements. In the early 2000s, technology's role in education primarily revolved around e-learning platforms and email communication, with online courses being relatively rare. However, from the mid-2000s onwards, a revolutionary shift occurred with the widespread adoption of Learning Management Systems (LMS) and the emergence of Massive Open Online Courses (MOOCs). These days, educational apps and interactive digital content have become commonplace. These platforms have ushered in a revolution in education by providing a versatile digital toolkit that goes beyond mere video lectures and interactive discussion forums. They now incorporate advanced assessment mechanisms, including machine learning-based grading. This revolution has paved the way for blended and online learning approaches, enhancing accessibility and flexibility in higher education. It is also undeniable that the COVID-19 pandemic in 2020 accelerated the adoption of remote and online learning technologies.